Perceptions of Students Towards The Scientist-Teacher-Student Partnership (STSP) in Medical Physics Subjects - Efwinda, Shelly; Nuryadin, Atin; Sulaeman, Nurul Fitriyah; Dzulfikar, Ahmad Zaki; Syafi’i, Ahmad (Universitas Negeri Semarang, 2025)
Medical Physics is a branch of physics application that is developing very rapidly. Therefore, the contextualization of Medical Physics is crucial for future physics teachers. This research aims to implement Student-Teacher-Scientist Partnerships (STSP) in Medical Physics and explore students' perceptions of the learning experience through this program. STSP in this research involved prospective physics teachers as students, lecturers in medical physics courses as teachers, and medical physicists as scientists. The benefits of this research are to provide a learning experience of medical physics directly from experts (medical physicists) as a provision for prospective physics teachers to strengthen their knowledge of medical physics content and how to teach it, and to be a recommendation for learning strategies that support contextual physics learning. Implementing STSP in medical physics courses includes planning, implementation, and evaluation activities for one semester of lectures; lectures by the foremost scientists were held in 7 meetings (1 meeting = 2 x 60 minutes). The planning stage includes activities to equalize perceptions between scientists and related lecturers. The course was primarily student-centred, with case study discussions conducted online via Zoom meetings. The scientists were located in East Java Province, Indonesia, while the teachers and students were in East Kalimantan Province, Indonesia. The evaluation stage was carried out by exploring students' perceptions of the program implementation, the results of which can later be used as a reference for the continuation of the program implementation. Results indicated that STSP activities facilitated easier comprehension of medical physics, increased interest in further study, and highlighted connections between course topics and secondary school curriculum.